Avaliação formativa: um olhar discente/docente sobre as práticas dos professores dos anos iniciais - SANTOS, Karine Cerdeira dos (2020)
This work presents partial results of a research project intituled “Learning assessment in Mathmatic classes in the early years of Elementary School: perceptions of undergraduates”, whose objective consisted on identifying and discussing, under the point of view of formative assessment, the evaluation process proposed by the teachers of forth and fifth year classes. In order to do so, this research is based on Fernandes (2008), who proposes a formative assessment; on Borralho, Lucena e Brito (2015), for whom the main objective of evaluation needs to be upgrading learnings; Perrenoud (1999), who proposes regulation to the learning levels, in order to individualize each one of them throw formative assessment; and Silva (2004), who writes about meaningful conceptions and about evaluative practices. This descriptive research is structured in: theoric studies; observation; discussion groups; questionary; and analysis of the empiric material. Ten undergraduateds of seventh semester who were studying the theme Teaching Stages II in the University course “Licenciatura Integrada em Ciências, Matemática e Linguagens” of UFPA, Belém-PA, participated. The analysis presented here show that all the teachers at the choosen schools for this research still think about evaluation dissociated from learnig-teaching process; besides that, according to them, the most important evaluation tools are the writing tests. At the end, this research shows that the undergraduates have developed some skills, according to three aspects: they amplyfied their conceptions of formative assessment; have changed their perception of indissocioability between teaching-learning-evaluation and their knowledge about evaluation tools.